Pengaruh Penambahan Kapur terhadap Nilai Plastisitas Tanah Lunak - Aisyah Salimah; Ighfar Qaribullah (Journal of Research and Inovation in Civil Engineering as Applied Science, 2022)
The native soil is subsoil with low plasticity, it has low slick-force properties, low permeability coefficient, and low backing. Land with low plasticity indexes has low supporting power when used as a basic foundation of both a road and a building that is a vital object, thus improving the soil. From the above problem, the research was intended to engineer original soil with a chalk mixture of four relative 0%,5%,10%, and 15%. The method used was in laboratory tests according to some ASTM standards. Each one was testing for properties and the value of the liquefied and plastic limits (Atterberg limit). From testing results obtained native soil according to the uses classification system, original soil belongs to low plastic-plated soils in the sedation to testing shows original soil has obtained a value of a plasticity index of 22.008%. While the results of the mixed soil test, the addition of lime can reduce the liquid limit value, plastic limit, and plasticity index.